Challenges and opportunities for teacher professional development in interactive use of technology in African schools - Hennessy, Sara; Haßler, Bjoern; Hofmann, Riikka (Technology, Pedagogy and Education, 2015)
This article examines the supporting and constraining factors influencing professional learning about interactive teaching and mobile digital technology use in low-resourced basic schools in sub-Saharan Africa. It draws on a case study of iterative development and refinement of a school-based, peer-facilitated professional learning programme (‘OER4Schools’) that integrated use of mobile technologies, digital open educational resources and interactive pedagogy. The research and development involved teachers in three Zambian primary schools and culminated in an extensive multimedia resource. Using an ecological framework, factors emerging were characterised at three levels: teacher, school, and the wider community and policy context. They include school organisation and leadership, teacher motivation and perceptions of opportunities for professional learning and change, teacher views of pupil capabilities, availability of resources, teacher collaboration, and viewpoints of parents and policymakers. [ABSTRACT FROM PUBLISHER]
Keywords: ADULTS; AFRICA; Article; CAREER development; Digital Technology; EDUCATION; EDUCATIONAL technology research; Interactive Pedagogy; Open Educational Resources; PRIMARY school teachers; Sub-Saharan Africa; Zambia; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2099892; __finaldtb; digital technology; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

Recommendation 7: Use ICT to provide access to content, professional development and professional learning communities - Lawrie, J.; Hennessy, Sara; Haßler, Björn; Phalachandra; Lawrie, J. (Where it's needed most: Quality professional development for all teachers, 2015)
Keywords: C:Fragile contexts; dode_eth-src-dode; dode_eth-trf2-dode